Logic equation simplification

boolean-algebradiscrete mathematicslogic

How it the following logic equation $$(B \land \lnot C) \lor (A \land B) \lor (A \land C)\tag 1$$ simplified into $$(B \land \lnot C) \lor (A \land C)\tag 2$$

I'm simplifying a boolean equation for a breadboard circuit-work and I've used a couple of online boolean equation simplifiers to verify my solution but I just can't seem to understand how the equation $(1)$ is simplified to equation $(2)$? What happened to $A \land B$? I'm not yet fully knowledgeable on certain boolean algebra laws. I would really appreciate it if someone could show a clear solution together with what law was used.

Best Answer

If $A\land B$ is true, then one of $A\land C$ or $B\land\neg C$ will also be true already, depending on the truth value of $C$.

So adding an $A\land B$ disjunct will not make the expression more true than it already was.

You can show this symbolically by $$ \begin{align} & (B\land \neg C) \lor (A\land B)\lor (A\land C) \\ ={}& (B\land \neg C) \lor [(A\land B)\land (\neg C\lor C)]\lor (A\land C) \\ ={}& (B\land \neg C) \lor (A\land B\land \neg C) \lor (A\land B\land C) \lor (A\land C) \\ ={}& [(B\land \neg C)\land(1\lor A)] \lor [(A\land C)\land(1\lor B)] \\ ={}& [(B\land \neg C)\land1] \lor [(A\land C)\land1] \\ ={}& (B\land \neg C)\lor (A\land C) \end{align}$$

Related Question